P1 Preliminary results for association of survival time in idiopathic pulmonary fibrosis cases with the 11p15.5 region. (12th November 2015) - Allen, RJ; Tobin, MD; Wain, LV; Braybrooke, R; Jenkins, G
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) is a restrictive lung disease of unknown cause. The median survival time after diagnosis is 3–5 years and there are limited treatments available. MUC5AC, MUC5B and TOLLIP in the 11p15.5 region have been shown to be associated with susceptibility to IPF. A variant in TOLLIP (rs5743890) has also been shown to be associated with both susceptibility and survival time however the effects were in opposite directions, i.e. the allele associated with increased susceptibility was also associated with increased survival time. Methods: We performed survival analysis on 612 European IPF cases passing QC using a Cox proportional hazards model adjusting for age, sex, first 10 principal components and study centre. 134 variants were genotyped in a 200 kb region on chromosome 11 covering MUC5AC, MUC5B and TOLLIP . Results: No SNPs in this region reached genome-wide significance (p < 5 × 10 –8 ). The most significant variant was rs56367042 (Hazard Ratio 3.38, 95% CI [1.91, 5.96]; p = 2.74 × 10 –5 ) which is located downstream of MUC5B . The next significant SNP was rs5743894 (Hazard Ratio 0.67, 95% CI [0.54, 0.83]; p = 2.24 × 10 –4 ) located in TOLLIP . For this SNP the allele we found associated with increased survival time has previously been reported as associated with increased susceptibility (showing a similar pattern to that reported for rs5743890) however this SNP has also been previously reported as not being associated with survival time. We found a proxy of rs5743890 (R 2 = 0.698) not to be associated with survival time (p = 0.881). Conclusions: Our results did not replicate those previously reported; however they may support the hypothesis that variants in TOLLIP that increase susceptibility may also increase survival time. In future we will perform a GWAS for susceptibility and survival time and try and replicate the findings.